Revitalization Model of Industrial Apprenticeship-Based Professional Competence for Light Vehicle Engineering Expertise Teachers of Vocational School - Bunyamin, Bunyamin; Samsudi, Samsudi; Ekosiswoyo, Rasdi (The Journal of Educational Development, 2018)
The revitalization of professional competencies aimed to increase the number and quality of the light vehicle engineering (TKR) teachers’ skills. The background of this study was the low absorption of human resources from the vocational school in the business world and industrial world (DU/DI), the lack of teacher expertise in teaching factory, and the gap between education and industrial demands. This study aimed to produce a revitalization model of professional competence based on industry apprenticeship that is ideal and effective for improving the competence of TKR productive teachers. This research employed Reseach and Development (R & D) Methods. The subject of this research was TKR Teachers in Semarang Municipality. The results of the preliminary study were analyzed using a qualitative descriptive technique. The development results, the model of readability tests, and the model tools were tested through expert judgment. The feasibility of the model was tested through forum group discussion (FGD) and evaluation, i.e. the industry effectiveness test or the professional certification body (LSP). The results of the research show the following. First, the competence of TKR productive teachers in the form of general competence is 31 - 71% and the core competency is 29 - 69% of the whole competencies that should be mastered by the teachers. Based on the empiric data, the teachers were then assigned to join an industry apprenticeship. After the industry apprentices, the teacher’s competence tests either through the industry test or the LSP test recommended that they were competent. It can be concluded that the competency revitalization model of industry-based professionals for vocational school teachers of the light vehicle engineering expertise is effective to improve the competence of the productive teachers' skills.